In vivo efficacy of human recombinant factor IX produced by the human hepatoma cell line HuH‐7. (15th May 2015) - Enjolras, N.; Perot, E.; Le Quellec, S.; Indalecio, A.; Girard, J.; Negrier, C.; Dargaud, Y.
<x xml:space="preserve">Abstract</x> Introduction Post‐translational modifications of the CHO‐cell‐derived‐recombinant human factor IX (FIX) currently used for the treatment of hemophilia B (HB) are different from plasma derived FIX. Our previous studies described a rFIX (HIX) having better profile of post‐translational modifications than rFIX produced by CHO cells. The aim of the study consisted to verify the improved post‐translational modifications effect of HIX on in vivo recovery. Materials and methods HIX has been produced in a bioreactor and then purified from supernatants. In vitro activation and activity were evaluated measured by thrombin generation tests (TGT) and compared to commercial molecules, Benefix®, Mononine®. The three molecules were then administrated (i.v.) to FIX‐knockout mice and two minutes after injection, blood samples were collected and subjected to human FIX‐specific‐ELISA and TGT. Results The clotting function of HIX, activation courses of HIX by FXIa and FVIIa‐TF complex appear normal as did activation of Benefix®, Mononine® and TG constants of each FIX were equivalent. After injection to HB mice, circulating HIX did not present any significant difference in term of antigen value with Benefix®. Intriguingly, TGT were clearly exhibiting a better velocity for HIX than Benefix® and Mononine®. These data suggested that HIX may improve in vivo coagulant efficacy in comparison with the two commercial FIX injected at the same dose. Conclusion The study shows that HuH‐7‐derived‐rFIX has better in vivo haemostatic activity in hemophilia B mice compared to the reference rFIX molecule despite similar in vivo recovery rates, suggesting that HuH‐7 cells could represent an effective cellular system for production of rFIX.